PUNCTUATED EQUILIBRIA: AN ANALYSIS OF HEALTHCARE UTILIZATION PATTERNS FOR OLDER ADULTS WITH CHRONIC DISEASE. (20th December 2022) - Crowley, Christopher; Stuck, Amy; McBride, A Camille; Andrews, Claire
Abstract: The growing population of older adults requires healthcare delivery models that are both cost effective and directed toward the higher rates of chronic conditions, frailty and functional impairment often present as one ages. Analyzing healthcare utilization patterns of older adults—especially those over the age of 75—will better inform how to re-design care delivery processes.While the presence of chronic conditions requires consistent treatment, the intensity of health services required on a day-to-day basis is highly variable. Many individuals with at-risk health status are remarkably stable, exhibiting high levels of function and low utilization of care over extended periods of time. Periodically, however, these phases are punctuated by catastrophic episodes that can lead to greater health decline, morbidity, and mortality. During cycles of health decline, a cascade of other challenges stemming from an individual's underlying risks, predispositions, and complexities can arise. This punctuated equilibrium of utilization for older adults offers insight to assess ways to improve care and lower costs. In this paper, we analyze and quantify both these states of punctuated equilibria as well as the extensive periods of stability. The associated utilization patterns are analyzed by processing Medicare claims data. Our analysis showed that over 80% of members in a group of anticipated high-risk Medicare beneficiaries over the age of 75 exhibited low utilization for 11 months out of a given year. These findings complement research exploring care redesign processes at a system level, specifically directed to high-cost episodes of care as opposed to patient-level targeting.